solve the question given above
Attachments:
![](https://hi-static.z-dn.net/files/df1/823f9b5aecbdc1bfb1e360eae7dd2d05.jpg)
Answers
Answered by
1
Answer:
hope this helps you to understand better
Attachments:
![](https://hi-static.z-dn.net/files/df6/489faa3ff419262e185cf9039f5a4f53.jpg)
Answered by
1
Answer:
2:3
Step-by-step explanation:
by componendo dividendo
(x³+12x+6x²+8)/x³+12x-6x²-8=(y³+27y+9
y²+27)/y³+27y-9y²+27
(x+2)³/(x-2)³=(y+3)³/(y-3)³
cube root both sides
(x+2)/(x-2)=(y+3)/(y-3)
(x+2)*(y-3)=(y+3)*(x-2)
xy-3x+2y-6=xy-2y+3x-6
4y=6x
2/3=x/y
2:3=x:y
Similar questions